TNFAIP8L3 regulation of the TGF-β signaling pathway affects the proportion of macrophages during tumor antigen presentation and affects the prognosis of ovarian cancer - Chaomin Yue; Xiao Zheng; Yuqing Ye; Danyang Li; Yanhong Zhou (Frontiers in Molecular Biosciences)
BackgroundOvarian cancer is a serious disease that is a danger to a woman’s life and health and is currently being extensively studied worldwide. TNFAIP8L3, a member of the tumor necrosis family, plays a significant role in tumor immune regulation; however, its role in ovarian cancer has not been fully studied and reported.MethodThis study used data from 381 cases of ovarian cancer (OVCA) from The Cancer Genome Analysis (TCGA)-OV to analyze the clinical phenotype and immune phenotype of TNFAIP8L3. Pearson correlation coefficients and protein–protein interaction (PPI) network analyses were used to identify potential biological functions and the genes co-expressed with TNFAIP8L3. The Gene Set Enrichment Analysis (GSEA) method was used to evaluate the relevant regulatory pathways of TNFAIP8L3. Gene Set Variation Analysis was performed to evaluate the proportions of 24 immune cell types in OVCA. Finally, a nomogram and multivariate COX regression analysis were performed to prove the independent prognostic value of TNFAIP8L3 in OVCA.ResultsA total of 181 genes were co-expressed with TNFAIP8L3, including 163 positively correlated and 18 negatively correlated genes. The co-expressed genes associated with TNFAIP8L3 were significantly enriched in biological processes such as cell activation involved in immune response and leukocyte activation involved in immune response. Pathway analysis of TNFAIP8L3 further revealed the association of TNFAIP8L3 with the TGF-β signaling pathway and antigen processing and presentation pathways, especially with macrophages and neutrophils in the antigen presentation process. Moreover, the expression of TNFAIP8L3 was significantly high in OVCA and other solid tumors to function as an independent risk factor for the prognosis of OVCA, with important research value for the prognosis of patients with OVCA.ConclusionThose findings indicate that TNFAIP8L3 is correlated with antigen processing and presentation pathways in macrophages and neutrophils and affects prognosis and immune infiltration in OVCA.